PROCESSING APPARATUS, OPTICAL INSPECTION SYSTEM, SUBJECT SURFACE IMAGE COMPOSITION METHOD, SUBJECT SURFACE IMAGE COMPOSITION PROGRAM - Kamikawa, Takahiro; Okano, Hideaki; Ohno, Akifumi; Ujihara, Yousuke; Takagi, Yoshiaki; Suzuki, Sayuri; Ohno, Hiroshi; Kano, Hiroya (2025)
According to an arrangement, a processing apparatus includes one or more processors. The one or more processors are configured to: shift one or more captured images selected from a plurality of captured images including a reference captured image, and compose at least one subject surface image by superimposing the shifted one or more captured images on the reference captured image. The plurality of captured images have been obtained with an imaging portion within a predetermined time while a surface of a subject moving relative to the illumination light is irradiated with a plurality of beams of illumination light traveling in different directions in at least one plane.